The Educational Character Based on Islamic Spirituality - Munjin Munjin; Windariyati Dyah Kusumawanti (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to produce a Character Education Model Based on Islamic Spirituality. To collect data, the methods used  are observation, interview, and documentation, and then analyzed by steps of reduction, display, and drawing a conclusion. The results illustrated that Islamic Spirituality-based character education is aimed to liberate students from materialism and secularism life; to educate students with three main positive characters: wisdom, courage, and Iffah; to integrate aspects of knowledge, habituation, interactive, and mental cultivation; and to educate the students' characters through conscience education (qalb). The character education was implemented by integrating teaching and learning, habituation, building a school atmosphere, and building cooperation with the family.